The biocontrol agent Streptomyces rimosus subsp. rimosus tempers shifts in the wheat spicosphere microbiome induced by Fusarium Head Blight - De Troyer, Larissa; Audenaert, Kris; Ommeslag, Sarah; Debode, Jane; De Gelder, Leen; De Zutter, Noémie (Frontiers in Plant Science, 2025)
IntroductionFusarium Head Blight (FHB) is a major fungal disease in wheat caused by Fusarium graminearum, inducing severe yield losses. Biological control agents (BCAs) can be an effective and sustainable approach to mitigate this phytopathogen. In this study, Streptomyces rimosus subsp. rimosus LMG19352 was used as a BCA to mitigate F. graminearum on wheat ears. Moreover, we aimed to assess the impact of BCA inoculation on non-target microorganisms present on the wheat spikes. Therefore, we evaluated shifts in the fungal and bacterial spicosphere microbiome (i) over time from flowering to mid-grain filling stage and (ii) across inoculations with F. graminearum and/or S. rimosus subsp. rimosus LMG19352.MethodsFHB symptoms were determined by multispectral imaging, and Illumina MiSeq was used to amplify 16S V3-V4 rDNA for bacteria and ITS2 for fungi, whereafter a correlation network analysis was performed.ResultsThe biocontrol potential of S. rimosus subsp. rimosus LMG19352 against F. graminearum was confirmed, as FHB symptoms were significantly reduced. Based on the microbial abundances, S. rimosus subsp. rimosus LMG19352 compensated for shifts in the spicosphere microbiome community induced by FHB. These results were supported by a network analysis, revealing a more complex and stable microbiome in the presence of the BCA compared to the infected control.DiscussionTo our knowledge, this study is the first to reveal the potential of a bacterial BCA to temper shifts in the wheat microbiome caused by a phytopathogen, and thereby acting as a promising BCA.